(3GdOQ GdfXje aj JSgjd GdJbhjes - (3GdQGUO , eMeO GdQGUO, Jbj GdOjf CHh HcQ,J (B993 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGgH Gdeff ef aVdg GdYeje hHYO adeG QCjJ Gdgee bO bUQJ Yf COQGc eYGfi ai GdMbGFb GdadcjI aUd ai eYQaI Jbhje GdTeS s
(3BNQgG (B:s
(3LOhd eMce YWGQO HQUO GdZ Hjc GdSeQbfOi s
(3GdfSNI HgG MhGTs
(3cJHJ gPg GdfSNI HQSe GdTjN SGde Hf MSjf Hf CMeO GdSHci HgG GdYOjO ef GdLOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B304s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B736s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs